2014
DOI: 10.1098/rspb.2013.2732
|View full text |Cite
|
Sign up to set email alerts
|

Community-level education accelerates the cultural evolution of fertility decline

Abstract: Explaining why fertility declines as populations modernize is a profound theoretical challenge. It remains unclear whether the fundamental drivers are economic or cultural in nature. Cultural evolutionary theory suggests that community-level characteristics, for example average education, can alter how low-fertility preferences are transmitted and adopted. These assumptions have not been empirically tested. Here, we show that community-level education accelerates fertility decline in a way that is neither pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 38 publications
(97 reference statements)
2
95
0
1
Order By: Relevance
“…There are many other proposed pathways whereby improving the social capital of women can motivate lower fertility (e.g. changing sources of social information or the status benefits to other behaviour) [36,37,83]. These explanations do not rely on a commitment to the fertility reduction itself reflecting a fitness-maximizing strategy.…”
Section: Re-evaluating the Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…There are many other proposed pathways whereby improving the social capital of women can motivate lower fertility (e.g. changing sources of social information or the status benefits to other behaviour) [36,37,83]. These explanations do not rely on a commitment to the fertility reduction itself reflecting a fitness-maximizing strategy.…”
Section: Re-evaluating the Empirical Literaturementioning
confidence: 99%
“…This has led some researchers to suggest that the nineteenth to twentieth century demographic transitions reflect female preferences for lower fertility [3,4], and furthermore that these preferences may reflect females' adaptive reproductive strategies for smaller family sizes [20,32 -35]. This is a nascent field of inquiry among evolutionists and the arguments are not yet well fleshed-out, but the empirical association between female education and lower fertility is well documented at both the individual and group levels [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Transparent social influence might come from an acknowledged village expert in a particular category [31], whereas less-intense influence might diffuse among passive members of village social networks, who might not necessarily adopt the behaviour themselves [32]. Among over 20 high-fertility communities in rural Poland, for example, Colleran et al [16] found that the low-fertility norms of educated women were learned socially by lesser educated women within the same social networks who were using the more-educated women as models.…”
Section: (A) the Map Quadrantsmentioning
confidence: 99%
“…[14]) those variables are seen as insufficient to change behaviour without the addition of social influence [15]. For example, in Poland, poor uneducated women living in a wealthy educated group tend to adopt the low-fertility level of the group rather than the higher fertility that otherwise would be associated with their low income and low education as individuals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the degree of genetic influence, even decisions that are strongly influenced by socially transmitted norms are useful to study from an evolutionary point of view [29,34]. The mind, culture and consciousness are also products of evolution.…”
Section: Introductionmentioning
confidence: 99%